2021
DOI: 10.3390/su13063142
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity and Corporate Social Performance in Different Industry Groups: Evidence from China

Abstract: This paper examines the heterogeneous links between board gender diversity and corporate social performance in different industries across China. OLS regression models are approximated using the data of Chinese industries from 2009 to 2015. Robustness test and two-stage least square (2SLS) methods are incorporated to cater for robustness and endogeneity. Board gender diversity (BGD) stimulates corporate social performance (CSP) of firms with environmental and social risk exposure regardless of critical mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 97 publications
(123 reference statements)
4
45
0
1
Order By: Relevance
“…Hypothesis (H2) results of model 2 show that political ties are also connected significantly negatively with the quality of CSR disclosure (t = −4.22, p < 0.000), consistent with H2 [71,98]. Hypothesis (H3) the results of model 3 demonstrate a positive linkage of shareholding with executive turnover influence on the quality of CSR disclosure (t = 21.03, p < 0.000) consistent with H3 [99,100]. Hypothesis (H1) in the model ( 4), the interaction is observed between the quality of CSR disclosure and executive turnover whereby the coefficient of the interaction term resulted in being significantly negative (t = −22.03, p < 0.000), depicting that ensuring quality of CSR disclosure decrease the effect of executive turnover, which supports H1 [71,101].…”
Section: Results and Analysissupporting
confidence: 69%
“…Hypothesis (H2) results of model 2 show that political ties are also connected significantly negatively with the quality of CSR disclosure (t = −4.22, p < 0.000), consistent with H2 [71,98]. Hypothesis (H3) the results of model 3 demonstrate a positive linkage of shareholding with executive turnover influence on the quality of CSR disclosure (t = 21.03, p < 0.000) consistent with H3 [99,100]. Hypothesis (H1) in the model ( 4), the interaction is observed between the quality of CSR disclosure and executive turnover whereby the coefficient of the interaction term resulted in being significantly negative (t = −22.03, p < 0.000), depicting that ensuring quality of CSR disclosure decrease the effect of executive turnover, which supports H1 [71,101].…”
Section: Results and Analysissupporting
confidence: 69%
“…Regarding the effect of gender diversity on CSP, the literature suggests a positive relationship. Several previous works [3,[34][35][36][37][38] point out that gender diversity on boards of directors is one of the determining factors of CSP. In addition, Landry et al [39] found that the higher the board gender diversity, the more likely the company appears on the lists of the most ethical companies as well as those of the best corporate citizens.…”
Section: Board Gender Diversity and Cspmentioning
confidence: 99%
“…According to the classification proposed by Kanter [59] it is essential to achieve a "tilted" group by having at least 30% women on the board of directors [66], which is equivalent in absolute terms to three women [67], to bring about significant, perceptible changes in group dynamics [68]. Based on these arguments, several studies have confirmed the need for representation of at least three women on the board in order for their presence to contribute positively to socially responsible actions [69] such as environmental initiatives and programmes [70]. However, some scholars disagree, reporting that reaching a critical mass of two women is sufficient to reduce GHG emissions [71] and ensure greater environmental innovation [72].…”
Section: Theories Of the Role Of Women On The Board Of Directors And The Influence Of Women On Csrmentioning
confidence: 99%